Insulin resistance and polycystic ovary syndrome - (:unkn) unknown (Nova Science Publishers, Inc., 2010)
Insulin resistance is commonly defined as decreased sensitivity or responsiveness to metabolic actions of insulin affecting between 10 and 25 % of the general population. Insulin resistance is associated with a clustering of metabolic disorders including hyperlipidemia, cardiovascular disease, diabetes mellitus, obesity and hypertension. Polycystic ovary syndrome (PCOS) is the most common hormonal disorder of reproductive aged women, affecting 5-10% of this population. Approximately 50- 70% of women with PCOS are insulin resistant. Insulin resistance is a cardinal finding in the pathophysiology of PCOS. Quantifying insulin senstivity/resistance is of great importance for studies and eventual use in clinical practice. Early detection of insulin resistance is crucial in the management of PCOS. An improvement of insulin resistance in PCOS ameliorates endocrine and reproductive functions. Though obesity increases insulin resistance by itself, both lean and obese women have significant insulin resistance that is independent of obesity. Insulin sensitivity has been shown to be increased by vitamin D supplementation. Serum vitamin D is significantly lower in obese than in non obese individuals. Obesity and insulin resistance aggravate hyperandrogenism. In addition to life style interventions (weight loss, diet and exercise) and treatment with insulin sensitizers vitamin D supplementation should be kept in mind. The relationship between insulin resistance and depression has been investigated. Treatment of depression might be a strategy in the prevention of type 2 diabetes mellitus. Psychological symptoms should be evaluated as well as clinical symptoms in the treatment of PCOS.PCOS is charactherized by chronic anovulation, hyperandrogenism, insulin resistance, obesity, infertility and increased risk of spontaneous abortion. Doppler analysis of uterine perfusion and ovarian stromal blood flow in PCOS may improve understanding failure of implantation and spontaneous abortion. Increased ovarian stromal blood flow and decreased uterine perfusion may be related to insulin resistance and increased androgens. Women with PCOS should undergo a comprehensive evaluation and must be closely monitored for deteriotion in glucose tolerence. Lifestyle modification is the first line therapy; combined oral contraceptives are the most often used treatment modality and insulin sensitizing agents are recent therapeutic strategy in women with PCOS. © 2010 Nova Science Publishers, Inc. All rights reserved.